Design of Automotive Product Seat Lifting Aids in Minimizing MSD Complaints using AHOQ Method (Case Study: Final Line of Automotive Industry Assembly Process) - Nelfiyanti Nelfiyanti; Ridhwan Adhitya Ibnimatiin; Annisa Mulia Rani; Wiwik Sudarwati; Anwar Ilmar Ramadhan (Faculty of Engineering Universitas Muhammadiyah Jakarta, 2021)
Along with the times, every human level and life will be upgraded automatically. Likewise, the company if it does not adjust to the times, it will be difficult to adjust. As with the production process, there will be differences from time to time. From time immemorial, doing work manually, and in the present era using technological tools. Lifting the car seat manually makes the operator complain of pain, due to the high production volume. To eliminate the complaints from these operators, a proposed tool design was made. The method used is Axiomatic House of Quality. In general, Axiomatic Design can help the product development process be more structured with a focus on design that fits the function of the product. The first step in this research is to collect input from customers. Then after getting input from the customer, it is converted into a customer attribute. Then, develop the concept by making several alternatives based on the combination table. Next, determine the design that will be used and carry out testing and coordinate with the user, namely the assembly operator. Finally, determine the specifications and final design of the tool for lifting a seat whose load exceeds the lifting standard. The results of this study are in the form of a design tool for lifting the seat which is expected to reduce complaints of pain to the operator. So that this design design makes the company a consideration for implementation.